Safety and efficacy of tyrosinase inhibition of Paeonia suffruticosa Andrews extracts on human melanoma cells. (20th March 2019) - Lin, Daphne; Wang, Sue‐Hong; Song, Tuzz‐Ying; Hsieh, Chang‐Wei; Tsai, Ming‐Shiun
Abstract: Introduction: The development of tyrosinase inhibitors is a hot research topic. Recently, the Chinese herb Paeonia suffruticosa Andrews, commonly named as Cortex Moutan (CM), was reported as being capable of reducing melanogenesis. We developed an A2058 human melanoma cell model to test the safety and efficacy of tyrosinase inhibition. The aim was to further clarify the bioactivities of CM extracts and paeonol for the purpose of skin whitening. Methods: The 1, 1‐diphenyl‐2‐picrylhydrazyl (DPPH) scavenging activity, total polyphenol and flavonoid contents, and in vitro tyrosinase inhibitory effects of water and ethanol CM extracts were determined. Cellular inhibitions of tyrosinase and melanin production were also evaluated. Results: Water and ethanol CM extracts were both shown to have strong DPPH scavenging abilities in a dose‐dependent manner. The polyphenol content was higher in the ethanol CM extract compared to the water extract, while the flavanone content was comparable. Kinetic analyses revealed that the ethanol CM extract and paeonol are noncompetitive tyrosinase inhibitors. The cellular melanin content and l ‐DOPA oxidation assays demonstrated that the ethanol CM extract was an appropriate alternative whitening agent to paeonol and arbutin in ultraviolet‐induced A2058 human melanoma cells. Conclusion: The results of this study suggest that a human cell model is more suitable for determining tyrosinase activity than mouse cell models for determining cellular tyrosinase activity and melanin production. The ethanol CM extract was also confirmed as a promising ingredient in sun protection and skin whitening cosmetics. Future work should focus on melanogenesis‐related gene expressions.